2019
DOI: 10.1088/1755-1315/268/1/012105
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness Analysis on Renewable Energy in Malaysia

Abstract: Renewable energy is growing rapidly and becoming a popular alternative source of energy. Malaysia is looking forward to achieve 50% implementation of renewable energy (RE) by 2050. Sustainable energy development has been related to environmental issues, which can be eradicated by replacing fossil fuels with natural resources such as hydropower, solar, and wind to generate electricity. Public awareness is important towards accomplishing the goal in implementing renewable energy. Thus, this study focused on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 17 publications
2
20
0
1
Order By: Relevance
“…Several previous studies such as Sá nchez-Franco et al (2007) define brand awareness as "the awareness of the brand name is the ability of a customer to remember or recognize that name relating to a class of products." Numerous authors also point out that companies should try to achieve the maximum possible association of the brand with the product, moving from total ignorance of the brand to, if possible, the confusion between the product and the brand -such as the Kleenex trademark with its tissues (Zakaria et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies such as Sá nchez-Franco et al (2007) define brand awareness as "the awareness of the brand name is the ability of a customer to remember or recognize that name relating to a class of products." Numerous authors also point out that companies should try to achieve the maximum possible association of the brand with the product, moving from total ignorance of the brand to, if possible, the confusion between the product and the brand -such as the Kleenex trademark with its tissues (Zakaria et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Many countries have implemented different policies, such as developing sustainable energy infrastructure, to enable them to generate a percentage of their energy needs from RE sources; however, they failed to achieve their targets for various reasons, including people's lack of awareness regarding RE (this factor prevailed) [12,13]. The global implementation of RE technologies is significantly hampered by "economic barriers" (where there is no investment in the infrastructure of RE technology) and "social barriers," which comprise the lack of awareness, information, as well as technological literacy among people [13]. This lack of awareness regarding the concepts and benefits (financial and ecological) of implementing RE creates uncertainties and an information gap for the public.…”
Section: Public Awareness Regarding Re Technologies and Conceptmentioning
confidence: 99%
“…According to the survey conducted by [155], it was found that most Malaysians are aware of the importance of renewables as an alternative source in replacing conventional fossil fuel generation. A high fraction of 98.8% of respondents agreed that the impact of having a renewable source could bring a positive impact towards the environment in terms of carbon emission and global warming.…”
Section: Public Awarenessmentioning
confidence: 99%
“…Through social media, it would be easier to obtain and share information from a single click on the device [155]. In the recent advancement of social media technologies, there are options to scope the target audience, which is specifically categorized by their demographic and geographical location.…”
mentioning
confidence: 99%